The Social Dimension Of Faith in Classical Kalam - Eraslan, Yunus (Scientific Journal of Faculty of Theology, 2020)
Although debates about the issues of faith in Islamic thought started in the early stages, generally the theoretical aspect of the issue came to the fore. However, as with other issues, matters of faith have not developed independently of social realities. In this context, two different views emerged in terms of faith according to their positioning. The traditionalist approach, which accepts behavior as an essential element of faith, has excluded the general public from this definition by proposing a narrowly comprehensive definition. On the other hand, the innovative approach, which treats behavior as a result of faith, sought to include as many members of society as possible in recognition by suggesting a more comprehensive and encompassing definition. This social aspect of the issue also affected other issues related to faith, resulting in the separation of factions from each other. In this article, social realities behind the theoretical debates emerging in the classical theoretical thought starting from the semantic analysis of the words of faith and Islam will be examined. As a result, emphasis will be put on the socially unifying and distinctive aspects of the concepts of faith and believer. In addition, the implications of these different points of view in religious life will be mentioned.